Quality of sexual life of women with urinary complaints in reproductive age and after menopause - (:unkn) unknown (UNIFAP – Universidade Federal do Amapá, 2017)
To compare the quality of sexual life of women with urinary incontinence during reproductive age and menopause, and to analyze epidemiological data, including gynecological and obstetric characteristics. Methods: Cross-sectional, descriptive, and quantitative studies that evaluated women with urinary symptoms who sought assistance at the female urology services of Women’s Hospital and received gynecological care and assessment according to the Golombok Rust Inventory of Sexual Satisfaction (GRISS)-Female version in Macapa City, from February to June 2013. Results: Stress urinary incontinence was the predominant symptom, with a prevalence of 94.1% in postmenopausal women and 87.8% in non-menopausal women. Vaginal deliveries were more predominant than cesarean deliveries (median: 3 > 1) in both groups. Statistical significance was observed in the frequency of sexual intercourse (p = 0,0217), sexual satisfaction (p = 0,0105), expression of feminine sensuality (p = 0,0293), dyspareunia (p = 0.0022), and anorgasmy (p = 0.0002). Conclusions: Urinary incontinence had a negative effect on female sexuality, especially when associated with advanced age, which resulted in a decline in the quality of life of the women in this study.
Keywords: Incontinência urinária; Urinary incontinence; Saúde da mulher; Women’s Health; CNPQ::CIENCIAS DA SAUDE::MEDICINA